Ta‘līm an-naḥwi al-qāʾimi ʿalā al-āyāti al-qurʾāniyyati litarqiyati fahmi ʿalāmāti al-iʿrābi ladā ṭullābi aṣh-ṣhaffi aṯs-ṯsāmini-5: dirāsati taṭhbīqiyyati bi-madrasati ḥifzhi al-qurʾāni al-mutawassiṭhati al- ahliyyati bil-muʾassasati al-islāmiyyati - Mario Bagus Sanjaya; Sahkholid Nasution (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This study aims to describe the implementation of Qur’anic verse-based grammar (nahwu) instruction in enhancing the understanding of i‘rāb signs among Grade VIII-5 students at a private junior high school for Qur’an memorization under the auspices of the Central Islamic Foundation. The researchers employed a qualitative descriptive approach, collecting data through observation, interviews, and documentation. The findings reveal that integrating Qur’anic verses as models in nahwu instruction effectively contributes to improving students’ contextual understanding of i‘rāb concepts. The study also highlights several supporting factors, including a school environment centered on Qur’an memorization, innovative teaching methods, and the availability of learning media. On the other hand, certain challenges were identified, such as variations in students’ prior knowledge, a dense academic schedule, and limited instructional time. This approach has proven to have a positive impact by making the study of nahwu more relevant to learners’ real-life contexts and serving as an effective means of delivering applied and contextual grammar learning.Kata kunci: Implementation, Nahwu instruction, I‘rāb signs, Qur’anic verses, Contextual learning